2012
DOI: 10.5582/ddt.2012.v6.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of DL-α-lipoic acid against cisplatin-induced nephrotoxicity and cardiotoxicity in experimental animals

Abstract: Cisplatin is a potent chemotherapeutic agent with a wide range of activities. Nephrotoxicity and cardiotoxicity represent it's major complication upon clinical use. The present study was carried out to evaluate the possible protective effect of DL-α-lipoic acid (LA) against cisplatin-induced nephrotoxicity and cardiotoxicity. Different groups of rats (n = 10) were administered either saline (control), cisplatin (10 mg/kg, i.p.), LA (100 mg/kg, i.p.) or their combination (LA 30 min prior to cisplatin administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Due to amphiphilic properties, ALA has more advantages compared with other antioxidants such as vitamin C and E. Interestingly, Lipoic acid and its reduced form, dihydrolipoic acid (DHLA) has a redox potential of −0.32 V while the redox potential of GSH/ GSSG is −0.24 V. This difference reflects the fact that ALA has a greater defense capacity against oxidative damage than does GSH and ALA is able to reduce oxidized glutathione to GSH (Dwivedi et al 2014;Gomes and Negrato 2014;Rochette et al 2013;Smith et al 2004). It displays antioxidant effects by scavenging ROS and regenerates other endogenous oxidized antioxidants to their active reduced form (Hussein et al 2012). Several studies have shown that ALA exert in models of disease characterized by an increase in oxidative stress, such as type 2 diabetes, Alzheimer and cardiovascular disease (Ahmed 2012;Henriksen 2006;Wollin and Jones 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Due to amphiphilic properties, ALA has more advantages compared with other antioxidants such as vitamin C and E. Interestingly, Lipoic acid and its reduced form, dihydrolipoic acid (DHLA) has a redox potential of −0.32 V while the redox potential of GSH/ GSSG is −0.24 V. This difference reflects the fact that ALA has a greater defense capacity against oxidative damage than does GSH and ALA is able to reduce oxidized glutathione to GSH (Dwivedi et al 2014;Gomes and Negrato 2014;Rochette et al 2013;Smith et al 2004). It displays antioxidant effects by scavenging ROS and regenerates other endogenous oxidized antioxidants to their active reduced form (Hussein et al 2012). Several studies have shown that ALA exert in models of disease characterized by an increase in oxidative stress, such as type 2 diabetes, Alzheimer and cardiovascular disease (Ahmed 2012;Henriksen 2006;Wollin and Jones 2003).…”
Section: Introductionmentioning
confidence: 95%
“…ALA may play a renoprotective role on cisplatin-induced nephrotoxicity through antioxidant and antiapoptotic mechanisms combined with the onset of mRNA expression of antioxidant genes. 26 In our study, SOD and CAT activities were significantly decreased in AK group compared with the control group; SOD and CAT activities were increased in ALA-treated group compared with AK group, but only CAT activity was statistically significant. There was no significant improvement in GPx activity.…”
Section: Discussionmentioning
confidence: 60%
“…The lower cellular infiltration and lower tissue damage in ALA treatment might be associated with its antioxidant properties. 9,26,27 These properties were important in its protective effect against oxidative renal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), hydrogen peroxide (H 2 O 2 ), Thiobarbituric Acid Reactive Substances (TBARS), and nitric oxide (NO) (15,16). Numerous studies reported that cisplatin has a potential to induce oxidative damage in heart tissue by causing peroxidation of the cell membrane and dysfunction of mitochondria (17,18).…”
Section: Introductionmentioning
confidence: 99%